SOME QUESTIONS OF IMPROVEMENT OF ARTICLE 193 OF THE CRIMINAL CODE OF THE REPUBLIC OF KAZAKHSTAN - Smagulov , Асылбек Айжарыкович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
The author of article points to relevance of improvement of the legislation in the sphere of legalization of income gained by a criminal way, both at interstate level, and at the level of interstate arrangements and need of further study of legal base.